Innovative Approaches to Arabic Vocabulary Learning for Islamic Senior High School Students with Lectora Inspire - Hijriyah, Umi; Edi, Relit Nur; Erlina, Erlina; Kesuma, Guntur Cahaya; Khodr, Tamer Sa’ad Ibrahim (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
Mastering vocabulary is essential for language acquisition, particularly in Arabic. This study aims to develop and evaluate the feasibility and effectiveness of AVLI (Arabic Vocabulary on Lectora Inspire) for grade X students at Baitul Jannah Integrated Islamic High School. Employing a research and development approach, this study utilized the ADDIE development model, which includes analysis, design, development, implementation, and evaluation phases. Data were collected through documentation, observation, interviews, questionnaires, and tests. The findings revealed that the Lectora Inspire-based mufradat learning media is deemed feasible, achieving a feasibility test score of 75% from material expert validators and 90% from media validators. User feedback was positive, with 86% of 106 respondents finding the learning media engaging. Moreover, AVLI proved effective in enhancing mufradat learning, evidenced by an increase in average student scores from 65.5 on the pretest to 85.5 on the posttest, a rise of 30 points. Consequently, this study concludes that Lectora Inspire-based learning media is both feasible and effective for teaching mufradat to grade X students, highlighting its potential implications for Arabic language education.